Clinical Profile and Treatment Outcome of Guillain-Barre Syndrome: A Three Year Tertiary Care Experience from Kerala - Balagopal, Krishnan; George, Ria Elsa; Koshy, Riya Ann (Nepal Journal of Neuroscience, 2025)
Introduction: Guillain Barre Syndrome or GBS is an acute immune mediated polyradiculoneuropathy which continues to be a serious problem worldwide ,causing respiratory insufficiency requiring mechanical ventilation in up to 30 percent of patients. This study aims to look at the clinico epidemiological profile and treatment outcome in GBS patients admitted in a tertiary level hospital in India.Methods: We conducted a retrospective study of adult patients with Guillain barre Syndome admitted  at MOSC Hospital Kolenchery, Kerala,  a tertiary care centre in south India, from January 2021 to January 2024. The case records of the study population were retrieved from medical records department and the clinical profile and outcomes were studied.Results: A total of 28 patients were recruited on the study of which 17 (61%) were male and 11 female. The mean age of the study population was found to be 50 years. A preceding history of infection was found in 68% of patients and included respiratory infections and gastroenteritis. Limb weakness was the most common symptom noted followed by sensory symptoms including pain and paraesthesiae in the extremities. Intravenous immunoglobulin was the most common treatment modality given in 65% of patients. The most common clinical variant was Acute Motor Axonal Neuropathy(AMAN)  seen in 54% of patients followed by the demyelinating and bulbar onset forms. Ventilatory support was needed in 18% of patients and no cases of mortality were reported in the study population. Good treatment outcomes as calculated by the Hughes disability grading was achieved in 71 % of patients. Significant association was found between male sex and good outcomes.Conclusions: Guillain Barre syndrome affects patients of  all ages with a male predominance and a preceding infection seen in the majority of patients. Axonal form of GBS is the most common variety seen and a good outcome is noted in the majority of patients.